PENGARUH TINGGI BADAN DAN KELENTUKAN PERGELANGAN TANGAN TERHADAP KEMAMPUAN PUKULAN SMASH DALAM PERMAINAN BULUTANGKIS - Naim, Muhammad Ishak; Herman, Herman; Amahoru, Nurul Musfira (UNIVERSITAS NEGERI MAKASSAR, 2020)
This study aims to determine: (1) The effect of height on the ability to hit smash in badminton games for SMAN 4 Soppeng students. (2) The effect of wrist flexibility on the smash ability in badminton games for SMAN 4 Soppeng students. This research is a descriptive research. The study population was all students of SMAN 4 Soppeng with a total sample of 30 students who were selected by random sampling. The data analysis technique used is descriptive analysis technique, data normality, linearity and regression tests using the SPSS version 16.00 system at a significant level of 95% or 0.05. Based on the results of data analysis, this study concludes that: (1) Height has a significant effect on the ability to hit smashes in badminton at SMAN 4 Soppeng students with a t-count value of 4,819 with a probability level of 0,000 <0.05; (2) Wrist flexibility has a significant effect on the ability to hit smash in badminton for students of SMAN 4 Soppeng with a t-count value of 4,819 with a probability level of 0,000 <0.05.